2022
DOI: 10.1177/10748407221100284
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of COVID-19 Public Health Measures on Community-Dwelling People Living With Dementia and Their Family Caregivers: A Longitudinal, Qualitative Study

Abstract: Since the onset of the COVID-19 pandemic, community-dwelling people living with dementia and their family caregivers have experienced many challenges. The unanticipated consequences of public health measures have impacted these families in a myriad of ways. In this interpretive policy analysis, which used a longitudinal, qualitative methodology, we purposively recruited 12 families in British Columbia, Canada, to explore the impacts of pandemic public health measures over time. Semi-structured interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Some research has already investigated this to an extent; a rapid review of evidence related to the impact of COVID-19 isolation measures on mental health among people with dementia found that most studies identified worsening behavioral and psychological symptoms of dementia (BPSD) (28). Some of the research found these results through subjective assessments made by caregivers (29), qualitative interviews of people with dementia and their caregivers (30,31), and across international contexts (32).…”
Section: Introductionmentioning
confidence: 99%
“…Some research has already investigated this to an extent; a rapid review of evidence related to the impact of COVID-19 isolation measures on mental health among people with dementia found that most studies identified worsening behavioral and psychological symptoms of dementia (BPSD) (28). Some of the research found these results through subjective assessments made by caregivers (29), qualitative interviews of people with dementia and their caregivers (30,31), and across international contexts (32).…”
Section: Introductionmentioning
confidence: 99%
“…Authors SAW, LK (PhD Candidate), HAC and GP are PhD-prepared social gerontologists with experience conducting LTC research with staff, residents and family carers (e.g., Cooke et al, 2022;Puurveen et al, 2018). Authors JB and AB are PhD-prepared nursing faculty who have extensive experience conducting research in LTCHs as well as the impact of COVID-19 on older adults and their family carers (e.g., Baumbusch et al, 2022;Bourbonnais et al, 2023). Previous intersectional research examining the nature and gendered aspects of family caregiving within LTC contexts prompted the current investigation.…”
Section: )mentioning
confidence: 99%
“…Some research has already investigated this to an extent; a rapid review of evidence related to the impact of COVID-19 isolation measures on mental health among people with dementia found that most studies identified worsening behavioral and psychological symptoms of dementia (BPSD) [ 33 ]. Some of the research found these results through subjective assessments made by caregivers [ 34 ], qualitative interviews of people with dementia and their caregivers [ 35 , 36 ], and across international contexts [ 37 ].…”
Section: Introductionmentioning
confidence: 99%